Maternal High-Fat and High-Salt Diets Have Differential Programming Effects on Metabolism in Adult Male Rat Offspring - Segovia, Stephanie A.; Vickers, Mark H.; Harrison, Claudia J.; Patel, Rachna; Gray, Clint; Reynolds, Clare M. (Frontiers in Nutrition, 2018)
Maternal high fat or high salt diets can independently program adverse cardiometabolic outcomes in offspring. However, there is a paucity of evidence examining their effects in combination on metabolic function in adult offspring. Female Sprague-Dawley rats were randomly assigned to either: control (CD; 10% kcal from fat, 1% NaCl), high salt (SD; 10% kcal from fat, 4% NaCl), high fat (HF; 45% kcal from fat, 1% NaCl) or high fat and salt (HFSD; 45% kcal from fat, 4% NaCl) diets 21 days prior to mating and throughout pregnancy and lactation. Male offspring were weaned onto a standard chow diet and were culled on postnatal day 130 for plasma and tissue collection. Adipocyte histology and adipose tissue, liver and gut gene expression were examined in adult male offspring. HF offspring had significantly greater body weight, impaired insulin sensitivity and hyperleptinemia compared to CD offspring, but these increases were blunted in HFSD offspring. HF offspring had moderate adipocyte hypertrophy and increased expression of the pre-adipocyte marker Dlk1. There was a significant effect of maternal salt with increased hepatic expression of Dgat1 and Igfb2. Gut expression of inflammatory (Il1r1, Tnfα, Il6, Il6r) and renin-angiotensin system (Agtr1a, Agtr1b) markers were significantly reduced in HFSD offspring compared to HF offspring. Therefore, salt mitigates some adverse offspring outcomes associated with a maternal HF diet, which may be mediated by altered adipose tissue morphology and gut inflammatory and renin-angiotensin regulation.